International experience in preventing violations by border guard authorities: The case of EU member states - Kushnir, Yaroslav (Jurnal Cita Hukum, 2026)
The relevance of this study is determined by the growing role of border services in preventing offenses amid the evolving security environment of the European Union and the implementation of integrated border management. For Ukraine, critically analyzing international experience is essential due to the ongoing armed aggression of the Russian Federation and institutional differences in its law enforcement system, which make full adoption of EU models impractical without considering national realities. The study aims to examine international practices in crime prevention within the law enforcement and administrative-jurisdictional activities of border services in EU member states bordering Russia, to identify possibilities and limits for adapting these practices to the State Border Guard Service (SBGS) of Ukraine. The object of the study is the social relations formed during law enforcement and administrative activities in crime prevention under integrated border management. Using comparative, formal, structural-functional, and systemic legal analysis, the study examines the concept and content of crime prevention, the role of integrated border management, and the functions of Frontex and EU acquis standards in forming common security approaches. Practices in Poland, Finland, Lithuania, Latvia, and Estonia are analyzed, highlighting differences in pre-trial investigation, procedural coercion, and migration policy. Mechanical transfer of EU models to Ukraine is deemed ineffective and risky under martial law. Instead, selective adaptation of functional elements—risk analysis, interagency coordination, and analytical tools—can enhance SBGS operations while maintaining existing power structures. Promising areas for adaptation include risk-based analytics, preventive measures, and coordinated operational practices, ensuring effective crime prevention in Ukraine.